Optical constants of Titan aerosols and their tholins analogs: Experimental results and modeling/observational data. (May 2015) - Brassé, Coralie; Muñoz, Olga; Coll, Patrice; Raulin, François
Abstract: Since Bishun Khare׳s pioneer works on Titan tholins, many studies have been performed to improve the experimental database of the optical constants of Titan tholins. The determination of the optical constants of Titan aerosols is indeed essential to quantify their capacity to absorb and scatter solar radiation, and thus to evaluate their role on Titan׳s radiative balance and climate. The study of the optical properties is also crucial to analyze and better interpret many of Titan׳s observational data, in particular those acquired during the Cassini–Huygens mission. This review paper critically summarizes these new results and presents constraints on Titan׳s aerosols optical constants. Finally, the information lacking in this field is highlighted as well as some possible investigations that could be carried out to fill these gaps. Abstract : Highlights: Review on the determination of Titan tholins refractive index. Review on constraints on Titan aerosols refractive index from observational data. Comparison between laboratory and observational refractive index data. Highlights on the spectral ranges that need to be more investigated in the future.